INFLUENCE OF SPORTS ON STATE OF PLANTAR PRESSURE (Fiep Bulletin - online, 2013)
The project is focused on plantar posture research among combative sportsmen. We concentrate on possible differences related to the type of pad used for specific sport.  After previous experience especially with softer surfaces can be expected negative effects on the foot arch and influence on plantar pressure distribution during normal walking. Most combative sports need soft surface for athletes so gyms are usually covered with the tatami. We assume surface specific interaction with supporting leg system: on the one hand, locomotion on a flexible thus partially unstable pad may lead to strengthen foot muscles, on the other hand pad after contact with sole makes foot arch support, which can lead to lack of stimuli for active involvement of muscles supporting foot arch. The aim of the project was to prove potential exposure combative sports on the soft ground on the state of foot arch and if possible to determine the nature of the action. The research was realized with pedobarographic platform Emed and it was established mainly the pressure distribution on planta pedis while walking, and consequently the static pressure distribution in standing. In the research was involved 30 respondents of which 15 perform karate and 15 aikido. Research was in the years 2009 - 2011 at FSpS MU Brno. Based on our data we can tell that karatist´s transverse and longitudinal arch has different shape compare to the arch of aikido combatants and there are also significant marks proving a possitive influence of solid pad used in this sport for the right posture of the foot arch. From orthopedic view we can claim, that pad has very favourable effect for arch and there is the question for public if there is any need of stimuli compensation for combative sportsmen using just soft surface.
Keywords: Kinesiology; martial arts; sport; health